2016
DOI: 10.1002/micr.30068
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell therapy to promote limb transplant functional recovery

Abstract: Bone marrow-derived MSC therapy appears to improve sensory function recovery in a rat limb transplant model. Published 2016. This article is a U.S. Government work and is in the public domain in the USA Microsurgery 37:222-234, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 62 publications
(97 reference statements)
2
20
0
Order By: Relevance
“…To ensure adequate number of MSCs home lesion site we administered both locally and systemically. The MSC dose and frequency used in this study was consistent with our own previous report [ 40 ] where we performed hind limb transplants in rats that involved sciatic nerve transection and repair followed by the administration of MSCs. Also, our protocol was similar to Yang et al [ 41 ] where they studied dual regeneration of muscle and nerve by intravenous injection of human-amniotic fluid-derived mesenchymal stem cells (5 × 10 6 for 3 days daily following surgery) in a sciatic nerve injury model.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…To ensure adequate number of MSCs home lesion site we administered both locally and systemically. The MSC dose and frequency used in this study was consistent with our own previous report [ 40 ] where we performed hind limb transplants in rats that involved sciatic nerve transection and repair followed by the administration of MSCs. Also, our protocol was similar to Yang et al [ 41 ] where they studied dual regeneration of muscle and nerve by intravenous injection of human-amniotic fluid-derived mesenchymal stem cells (5 × 10 6 for 3 days daily following surgery) in a sciatic nerve injury model.…”
Section: Methodssupporting
confidence: 83%
“…Nerve transection and repair was done on the right hind limb, and the contralateral limb served as a non-transected (naïve) nerve control. Starting ≥1 week post-SNR or INR, animals received manual physiotherapy for the right hind limb (≤5 min, 1–2 times per week) as described previously [ 40 ]. Primary outcome measures were limb sensory and motor functions, and secondary outcome measures were gastrocnemius mass, flexion contractures, and nerve histology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lethal side effect of immunosuppressants raises the threshold of hand, face, and skin transplantations, which do not involve life‐threatening conditions. Combined immunosuppressive agents or BMMSCs, ADMSCs, and other cell therapies have been reported to have immunomodulatory effects in various transplantation models and to even promote functional recovery in rodent animals (Adamson et al, ; Fitzpatrick, Dehart, Brown, & Salgar, ; Plock et al, ; Radu et al, ; Siemionow & Nasir, ; Song, Muramatsu, Kurokawa, & Taguchi, ). Recent studies have also reported that rat iMSCs and human iMSCs have the potential of anti‐inflammatory effects in animal models (Ko et al, ; Lian et al, ; Wang et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Scale bars: 50 μm. ADMSCs, adipose-derived MSCs; BMMSCs, bone marrow-derived MSCs; hAD, human ADMSCs; hBM, human BMMSCs; hiM, human iMSCs; MSCs, mesenchymal stem cells; iMSCs, iPSCsderived mesenchymal stem cells; iPSCs, induced pluripotent stem cells; rAD, rat ADMSCs; rBM, rat BMMSCs have immunomodulatory effects in various transplantation models and to even promote functional recovery in rodent animals (Adamson et al, 2007;Fitzpatrick, Dehart, Brown, & Salgar, 2017;Plock et al, 2015;Radu et al, 2016;Siemionow & Nasir, 2007;Song, Muramatsu, Kurokawa, & Taguchi, 2005). Recent studies have also reported that rat iMSCs and human iMSCs have the potential of anti-inflammatory effects in animal models (Ko et al, 2018;Lian et al, 2010;Wang et al, 2018;Yang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%